Controlling Soil-Borne Disease in Soybean With a Mustard Cover Crop - G. F. Sassenrath; C. Little; K. Roozeboom; X. Lin; D. Jardine (Kansas Agricultural Experiment Station Research Reports, 2019)
Charcoal rot is a soil-borne disease that is prevalent in southeast Kansas. The disease infects multiple crops, including soybean, and causes yield reductions. A high-glucosinolate mustard with biofumigant properties reduced the population levels in soil and in soybean plants of the fungus (Macrophomina phaseolina) that causes charcoal rot. In this study, management practices that incorporate use of mustard as a cover crop in soybean production systems were tested. Results indicate that tillage increases the charcoal rot fungus. The mustard cover crop was tested in field studies for its impact on soil health, fungal disease and propagules, and soybean growth and yield.
Keywords: soybean; charcoal rot; cover crops